Incidence and Management of Thrombotic and Thromboembolic Complications Following the Norwood Procedure: A Systematic Review. (November 2017) - Agarwal, Arnav; Firdouse, Mohammed; Brar, Nishaan; Yang, Andy; Lambiris, Panos; Chan, Anthony K.; Mondal, Tapas K.
Background: The stage 1 Norwood procedure and its variants represent the first step of palliation for hypoplastic left heart syndrome. Although appropriate postoperative thromboprophylaxis is integral, significant variance remains across institutional practices. The purpose of this systematic review is to estimate the incidence of thrombosis and thromboembolism following the Norwood or modified Blalock-Taussig shunt procedure and examine current thromboprophylaxis regimens. Methods: Ovid MEDLINE and Embase were searched from January 2000 to June 2016 for primary studies explicitly reporting incidence of thrombosis, thromboembolism (strokes and pulmonary embolisms), or shunt occlusion in neonates, infants, and children undergoing the Norwood procedure or any variant. All-cause mortality was a secondary outcome of interest. Results: Of 887 identified articles, 15 cohort studies were deemed eligible, the majority including modified Blalock-Taussig shunt patients. Reported incidence of thrombosis ranged from 0% to 40%; thromboembolic events were rarely reported. Overall mortality ranged from 4.5% to 31.3% across studies. Although most studies involved the long-term acetylsalicylic acid use, thromboprophylaxis strategies varied across studies. Due to substantial variability in event rates, no correlation was identified with thrombotic complications. Discussion: Clinical practice guidelines recommend that patients receive intraoperative unfractionated heparin therapy and either aspirin or no antithrombotic therapy postoperatively. Our findings suggest a substantial risk of thrombosis and thromboembolism and demonstrate substantial variation in thromboprophylaxis practices. Conclusion: Although postoperative thromboprophylaxis seems optimal, it remains controversial whether the long-term aspirin use is most effective. Our findings highlight the lack of a gold-standard thromboprophylaxis strategy and emphasize the need for more consistency.